(untitled) (Ta’limning zamonaviy transformatsiyasi, 2025)
Recent years have been marked by a rapid development of technologies related to the use of electromagnetic fields and radio frequency radiation (RF EMR) in production and the environment. These systems, designed to transmit information, are usedтin various sectors of the national economy.